Vacuolar Localization of Wound-Induced Carboxypeptidase Inhibitor in Potato Leaves - Holländer-Czytko, Heike (1985)
The wound-induced carboxypeptidase inhibitor in potato leaves was shown to be localized in the central vacuoles of the cells. The inhibitor was quantified by immunological assays (ELISA) in protoplasts and vacuoles isolated from upper unwounded leaves of 5- to 6-week old potato plants that had been wounded on their lower leaves 48 hours earlier to induce the accumulation of the carboxypeptidase inhibitor. The regulation of the synthesis and compartmentation of the inhibitor is similar to that of wound-induced serine proteinase Inhibitors I and II in potato and tomato leaves and appears to be part of an induced defense response against attacking pests.